Indonesia’s Creative Economy Agency’s Communication Strategy in Supporting Creative City - Prayudi Prayudi; Kartika Ayu Ardhanariswari; Ninik Probosari (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2022)
The creative economy as the basis for a city to grow has led to a concept of creative city. Communication and support from all stakeholders, including the government, economic actors, academics, and the community, are necessary to foster creative behavior in the city’s economy. This paper examined the Indonesian government’s role through its creative economy agency in engaging relevant stakeholders through its communication campaign program. This paper employed a qualitative research analysis to identify the communication strategy. Interview, participatory observation, and library study were data collection tools. The research finding shows that the creative economy agency adopted the communication campaign strategy, consisting of situation analysis, plan, implementation, and assessment. A campaign program called “socialization and facilitation of registration of intellectual property rights for creative economic actors” had enabled creative actors to build awareness regarding the necessity of having their intellectual property protected, which becomes the basis for the creative city.